Toward performance portability of the Albany finite element analysis code using the Kokkos library. (March 2019) - Demeshko, Irina; Watkins, Jerry; Tezaur, Irina K; Guba, Oksana; Spotz, William F; Salinger, Andrew G; Pawlowski, Roger P; Heroux, Michael A
Performance portability on heterogeneous high-performance computing (HPC) systems is a major challenge faced today by code developers: parallel code needs to be executed correctly as well as with high performance on machines with different architectures, operating systems, and software libraries. The finite element method (FEM) is a popular and flexible method for discretizing partial differential equations arising in a wide variety of scientific, engineering, and industrial applications that require HPC. This article presents some preliminary results pertaining to our development of a performance portable implementation of the FEM-based Albany code. Performance portability is achieved using the Kokkos library. We present performance results for the Aeras global atmosphere dynamical core module in Albany. Numerical experiments show that our single code implementation gives reasonable performance across three multicore/many-core architectures: NVIDIA General Processing Units (GPU's), Intel Xeon Phis, and multicore CPUs.